2015
DOI: 10.1371/journal.pone.0136596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic and Conventional Management on Bio-Functional Quality of Thirteen Plum Cultivars (Prunus salicina Lindl.)

Abstract: In this study, thirteen Japanese plum cultivars (Prunus salicina Lindl.) grown under conventional and organic conditions were compared to evaluate the influence of the culture system on bioactive compounds. Their organic acids content (malic, citric, tartaric, succinic, shikimic, ascorbic and fumaric acid), total polyphenols, total anthocyanins, total carotenoids and antioxidant capacity (FRAP, ABTS) were evaluated. The study was performed during two consecutive seasons (2012 and 2013) in two experimental orch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Cuevas et al, 2015 [120] Organic plums had 5-10% higher antioxidant capacity than conventional fruit.…”
Section: Citation Major Conclusionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cuevas et al, 2015 [120] Organic plums had 5-10% higher antioxidant capacity than conventional fruit.…”
Section: Citation Major Conclusionmentioning
confidence: 97%
“…Karlund et al [121] found that the sensory qualities of strawberries produced under different cultivation systems varied mostly to due to genotype. Cuevas et al [120] identified one plum variety with superior production of total phenolic compounds and total organic acid content under organic management compared to the other twelve accessions tested. Lombardo et al [114] also identified a potato variety that presented greater total phenols and ascorbic acid than the other varieties tested when produced under organic practices.…”
Section: Citation Major Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic biosynthesis in plants is known to be strongly affected by the cultivar, the environmental conditions (especially light), as well as the type of fertilization [14,15]. Previous studies demonstrate that the organic fruits have higher phenolic content than conventional ones [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Plums are an important source of fibre and antioxidants (Stacewicz-Sapuntzakis et al 2001;Kim et al 2003). Moreover, organic plums have been described to harbour higher anthocyanin and polyphenol concentrations and greater antioxidant capacities (Cuevas et al 2015). Reserves in deciduous fruit trees consist mainly of carbohydrates, and to a lesser extent, nitrogen (Tromp 1983).…”
mentioning
confidence: 99%